2009
DOI: 10.3928/15394492-20090501-02
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure, Reliability, and Convergent Validity of the Engagement in Meaningful Activities Survey for Older Adults

Abstract: This study evaluated the psychometric properties of the Engagement in Meaningful Activities Survey (EMAS) (Goldberg, Brintnell, & Goldberg, 2002) in a sample of older adults living in the greater Los Angeles area. The EMAS evidenced moderate test-retest reliability (r = .56) and good internal consistency (α = .89). Exploratory factor analysis (principal components) discerned a twocomponent structure within the EMAS, indicative of Personal-Competence and SocialExperiential meaning. The EMAS demonstrated theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 49 publications
1
33
2
Order By: Relevance
“…Secondary analyses were conducted on a combined sample of 276 persons from two prior studies (Eakman, 2011; Eakman, et al, 2010a). These two samples were evaluated collectively to test the utility of the EMAS across a greater range of ages than could be addressed with just one of the samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary analyses were conducted on a combined sample of 276 persons from two prior studies (Eakman, 2011; Eakman, et al, 2010a). These two samples were evaluated collectively to test the utility of the EMAS across a greater range of ages than could be addressed with just one of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…The scale has demonstrated positive relationships with measures of life satisfaction and health-related quality of life, and negative relationships with measures of boredom, depression, and negative affect in community and institutional dwelling older adults, persons with persistent mental illness, and university students, (Eakman, 2011; Eakman, Carlson, & Clark, 2010a, 2010b; Goldberg, et al, 2002; Zimolag & Krupa, 2009). The EMAS has been related to measures of activity meaning, meaning and purpose in life, and basic psychological needs (e.g., relatedness, competence, and autonomy) thereby supporting its criterion-related and convergent validity.…”
Section: Introductionmentioning
confidence: 99%
“…Goldberg, et al, (2002) had suggested the EMAS evidenced sound psychometric properties, though additional studies are surely warranted to support the construct validity of the EMAS (Pedhazur & Schmelkin, 1991; Streiner & Norman, 2003). This paper involves the secondary analysis of data originally reported in a prior publication (Eakman, 2007). This study sought to establish the factor structure of the EMAS, and it was hypothesized that the EMAS would demonstrate sufficient psychometric properties as a measure of meaningful activity.…”
mentioning
confidence: 99%
“…Prior exploratory factor analytic results from a related scale, the Engagement in Meaningful Activities Survey (54), found correlated components thereby offering evidence to suggest that items underlying the OVal-pd might also be correlated. The present study supported this understanding because the four OVal-pd components demonstrated low to moderate intercorrelations.…”
Section: Discussionmentioning
confidence: 99%